2017
DOI: 10.1021/jacs.7b05414
|View full text |Cite
|
Sign up to set email alerts
|

A Bifunctional Reagent Designed for the Mild, Nucleophilic Functionalization of Pyridines

Abstract: Herein is reported the design and application of a reagent for the direct functionalization of pyridines. These reactions occur under mild conditions and exhibit broad functional group tolerance, enabling the late-stage functionalization of drug-like molecules. The reagent can be easily prepared on large scale from inexpensive reagents, and reacts in the title reaction with acetonitrile, sodium chloride, and sodium methanesulfonate as the sole byproducts. Although this Communication focuses primarily on reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 46 publications
(17 reference statements)
1
48
0
Order By: Relevance
“…Key geometrical data for 11-14 and known oxime sulfonate crystal structures are compiled in Table 1. (15) 107.20 (11) 111.48 (8) -176.27 (10) 11 S2 branch 1.2844 (18) 1.4372 (15) 107.88 (11) 111.98 (8) 174.10 (9) 12 S1 branch 1.2828 (18) 1.4380 (14) 108.64 (11) 109.65 8-169.20 (9) 12 S2 branch 1.2846 (17) 1.4427 (13) 108.26 (10) 110.13 7169.22 (9) 12 S3 branch 1.2840 (17) 1.4347 (13) 108.96 (10) 110.23 7-175.69 (8) 12 S4 branch 1.2839 (17) 1.4399 (13) 107.89 (10) 110.99 7 Crystallographic Abbreviations: It may be seen that the C=N and N-O distances of the oxime groups in 11-14 and in other known oxime sulfonate crystal structures [20][21][22][23] are all very consistent, as are the C=N-O and N-O-S bond angles. The C=N-O-S torsion angles indicate a preference for near planarity for these atoms, which is assumed to be the most stable conformation for oximes 24 and any small deviations might be ascribed to packing forces in the crystal.…”
Section: X-ray Single Crystal Structuresmentioning
confidence: 99%
“…Key geometrical data for 11-14 and known oxime sulfonate crystal structures are compiled in Table 1. (15) 107.20 (11) 111.48 (8) -176.27 (10) 11 S2 branch 1.2844 (18) 1.4372 (15) 107.88 (11) 111.98 (8) 174.10 (9) 12 S1 branch 1.2828 (18) 1.4380 (14) 108.64 (11) 109.65 8-169.20 (9) 12 S2 branch 1.2846 (17) 1.4427 (13) 108.26 (10) 110.13 7169.22 (9) 12 S3 branch 1.2840 (17) 1.4347 (13) 108.96 (10) 110.23 7-175.69 (8) 12 S4 branch 1.2839 (17) 1.4399 (13) 107.89 (10) 110.99 7 Crystallographic Abbreviations: It may be seen that the C=N and N-O distances of the oxime groups in 11-14 and in other known oxime sulfonate crystal structures [20][21][22][23] are all very consistent, as are the C=N-O and N-O-S bond angles. The C=N-O-S torsion angles indicate a preference for near planarity for these atoms, which is assumed to be the most stable conformation for oximes 24 and any small deviations might be ascribed to packing forces in the crystal.…”
Section: X-ray Single Crystal Structuresmentioning
confidence: 99%
“…Two encouraging reports appeared in the recent literature one each by the groups of Fier [15] and Paton [16] describing the transition metalfree direct cyanation approach. Two encouraging reports appeared in the recent literature one each by the groups of Fier [15] and Paton [16] describing the transition metalfree direct cyanation approach.…”
Section: Introductionmentioning
confidence: 99%
“…Various reagents like dimethyl sulphate, [17] N,N-dimethylcarbamoyl chloride, [18] ethyl chloroformate, [19] benzoyl halides, [20] acetic anhydrides, [21] and MsCl, [22] have been used as activators for this purpose [more recently, Sun and coworkers used hypervalent iodine (III) [23] as an activating agent]. [15,16,25] Therefore, it is apparent that these particular method- ologies need not only high cost but have environmental issues. In addition, these reagents are often hazardous, toxic, and sensitive towards air and moisture, which stiffen easy handling.…”
Section: Introductionmentioning
confidence: 99%
“…[12] In 2017, P. S. Fier reported that cyanation of pyridine used NaCN as an cyanation reagent with a-chloro O-methanesulfonyl aldoximes as an activator under mild conditions (Scheme 1e). [13] However, NaCN as a toxic cyanation reagent was required. In 1983, Fife reported N,N-dimethylcarbamoyl chloride could be used as an activation reagent for the cyanation of the pyridine N-oxides with TMSCN in dichloromethane.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the use of nonpolar solvents toluene and DCE gave relatively good yields of 2 a(Table 1, entries 11-12), wherein, DCE gave the most significant increase of product in 73% yields. Upon a comparison of different reaction temperatures, we found that 80 8C is to be optimal (Table 1, entries[13][14]. However, a continued increase in temperature to 100 8C failed to improve the reaction, which was probably due to fast decomposition of PhI (OAc) 2 .…”
mentioning
confidence: 95%